CLIMBING ON A SPACE IN THANHHA LAI’S NOVEL INSIDE OUT AND BACK AGAIN (2011) - Yesmawati Zai; Kurnia Ningsih; Desvalini Anwar (Universitas Negeri Padang, 2017)
This study is the result of the analysis of the novel of Inside Out and Back Again (2011) written by Thanhha Lai. Topics covered are how the business of women from her childhood in reaching the realm to show her existence in the social environment. The issues raised are the extent to which the protagonist expresses the realm accession process to demonstrate its ability, as well as how far the function of fiction elements, such as setting and conflict influential to demonstrate the business. Results of this study is to discover the extent of the protagonist reaches the realm of effort in showing her abilities, and to investigate the role of setting and plot in helping determine those efforts. The theory used in this analysis is the feminist concept of Trinha Minh-ha and psychosocial concept of Richard Lazarus and Susan Folkman. Assessment method used is text-based interpretation and context-based interpretation. The results of this analysis indicate that women from an early age can achieve a wider sphere to show his ability by way of awareness of differences and turn them into concrete efforts and spur him to learn more.